Same‐day antiretroviral therapy initiation hub model at the Thai Red Cross Anonymous Clinic in Bangkok, Thailand: an observational cohort study. Issue 12 (30th December 2021) - Seekaew, Pich; Phanuphak, Nittaya; Teeratakulpisarn, Nipat; Amatavete, Sorawit; Lujintanon, Sita; Teeratakulpisarn, Somsong; Pankam, Tippawan; Nampaisan, Oranuch; Jomja, Pintip; Prabjunteuk, Chotika; Plodgratoke, Prapaipan; Ramautarsing, Reshmie; et al.
Abstract: Introduction: WHO has recommended rapid antiretroviral therapy (ART) initiation, including same‐day ART (SDART). However, data on the feasibility in real‐world settings are limited. We implemented a cohort study at a stand‐alone HIV testing centre to examine its applicability and effectiveness. Methods: Data were collected from the Thai Red Cross Anonymous Clinic in Bangkok, Thailand, between July 2017 and July 2018 from clients who were ART‐naïve and could return for follow‐up visits. Baseline laboratory tests and chest X‐ray were performed according to national guidelines, and clinical eligibility was determined based on physical examination and chest X‐ray findings. Primary outcomes were retention in care and viral load suppression at 3, 6 and 12 months. Results: During the study period, 2427 people tested HIV positive. Of these, 2107 (2207/2427, 86.8%) met logistical criteria, and 1904 (1904/2427, 78.5%) agreed to SDART. One thousand seven hundred and twenty‐nine (1729/2427, 71.2%) were placed on ART, with 1257 received same‐day initiation and 1576 initiated ART within 7 days; 1198 clients were successfully referred to free, sustained ART sites. Retention among eligible clients who accepted SDART service at months 3, 6 and 12 was 79.8%, 75.2% and 75.3%, respectively. Conclusions: Same‐day ART initiation hub model at a stand‐alone HIV testing centre in an urban setting in Bangkok, Thailand, is highly feasible and has a potential for scaling up. Clinical Trial Number: NCT04032028